2019
DOI: 10.3390/su11113162
|View full text |Cite
|
Sign up to set email alerts
|

Energy Management and Operational Planning of an Ecological Engineering for Carbon Sequestration in Coastal Mariculture Environments in China

Abstract: China is now accelerating the development of an ecological engineering for carbon sequestration in coastal mariculture environments to cope with climate change. Artificial upwelling as the ecological engineering can mix surface water with bottom water and bring rich nutrients to the euphotic zone, enhance seaweed growth in the oligotrophic sea area, and then increase coastal carbon sequestration. However, one of the major obstacles of the artificial upwelling is the high energy consumption. This study focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The rising bubble plume transports the nutrient-rich bottom water or porewater to the surface, which can enhance the nutrient concentration in the euphotic layer. The detailed structure can be found in Lin et al (2019) [15]. In this experiment, the total area of kelp aquaculture is 48,000 m 2 , of which 8400 m 2 are attributable to the artificial upwelling distribution area.…”
Section: Ecological Engineering By Artificial Upwellingmentioning
confidence: 85%
See 1 more Smart Citation
“…The rising bubble plume transports the nutrient-rich bottom water or porewater to the surface, which can enhance the nutrient concentration in the euphotic layer. The detailed structure can be found in Lin et al (2019) [15]. In this experiment, the total area of kelp aquaculture is 48,000 m 2 , of which 8400 m 2 are attributable to the artificial upwelling distribution area.…”
Section: Ecological Engineering By Artificial Upwellingmentioning
confidence: 85%
“…Further work will have to determine the influence of the water turbidity, tidal current velocity, and other factors on the air-lift efficiency. Actually, we have done some preliminary research in this area, the detailed information can be found in Lin et al (2019) [15].…”
Section: Engineering Feasibilitymentioning
confidence: 99%
“…It was supported strongly by the Japanese government and the local fisherman cooperative organizations, so the technology matured in regard to operation practice for the last ten years. However, there are also some drawbacks, including (1) it is not cost-effective in practice; (2) the working range of the DCG system is limited by the topography, therefore, if it is applied in enclosed and semi-enclosed water body, the DCG system will get very good effects; (3) The complex mechanical and electrical system and its active control system is needed as the reliability and safety is a big problem in the ocean [79]; (4) the long pipe may be twisted or broken.…”
Section: Discussionmentioning
confidence: 99%
“…An unstructured grid finite-volume coastal ocean model (FVCOM) was used to understand the effect of the artificial upwelling. This model was developed originally by Chen et al [23] and efficient in resolving complex estuaries and coastal oceans dynamics. The unstructured triangular grid system can successfully embody the islands and barriers with complex topographies.…”
Section: Introductionmentioning
confidence: 99%